THE ROLE OF RADIOTHERAPY DELAY IN THE CHEMORADIATION TREATMENT FOR STAGE III INOPERABLE NON-SMALL CELL LUNG CANCER - E. P. Solov’eva; S. M. Asakhin; M. Ju. Val’kov (Сибирский онкологический журнал, 2016)
Introduction. One third of non-small cell lung cancer (NSCLC) patients have locally advanced inoperable Stage III tumors. Increasing number of induction chemotherapy (iCT) cycles may lead to delay of the start of radiotherapy (RT) and decrease survival. Objective. To evaluate a clinical impact of the starting time of RT among Stage III NSCLC patients after iCT on overall survival (OS). Materials and methods. The OS was calculated in patients, receiving radical RT during or later than 150 days after starting of iCT (RT150). Kaplan-Meier method with log-rank for intergroup comparisons was used. Correction for initial factors was made using Cox regression. Results. Overall, 49 patients with stage III NSCLC who received RT after iCT were selected. Twenty-five patients were irradiated during the period less then 150 days after the start of iCT, while other 24 – in more than 150 days. At distribution analysis, in the group RT>150 was higher proportion of patients with T4 (p=0.029) and with B stage (P=0.003), the other initial factors were distributed uniformly. The median (Me) OS was 19.9 (95 % confidence interval (CI) 16.8-23.2) and 21,0 (95 % CI 14.9-27.2) months, c2=0,017, p=0.895 in groups RT>150 and RT≤150, respectively. Me OS was 22.5 (95 % CI 10,2-34.9), 18.9 (95 % CI 16.9-20.9), and 18.4 (95 % CI 15.4-21.4) months, c2=4,42, P=0.110 for patients receiving 2, 3-4, 5 or more courses of induction CT, respectively. Hazard ratio (HR) of death in patients with a longer interval before the end of RT was 1.041 (95 % CI 0,571-1,897) and 1.485 (95 % CI 0,691-3,189) in univariate and multivariate analysis, respectively. Conclusion. In a retrospective analysis the delay of RT start after iCT leads to non-significant decrease of survival. More than two courses of iCT are not appropriate. The results need to be confirmed in a prospective randomized trial.